Physical-chemical and radiation properties of mountain streams - Richardson, Stuart, author; Striffler, William D. (William David), advisor; Meiman, James R. (James Richard), committee member; Vincent, Robert E., committee member (Colorado State University. Libraries, 1969)
Studies of bacterial fluctuation in mountain streams indicate pronounced seasonal and diurnal variations. This study attempt to determine seasonal and diurnal variation in (1) physical and chemical stream properties, and (2) solar radiation attenuation within the stream. Physical-chemical parameters measured included ammonium nitrogen, nitrate, nitrite, ortho-phosphate, meta phosphate, total dissolved solids, specific conductance, pH, dissolved oxygen, turbidity and temperature. Study sites were two natural high altitude streams in the Colorado Rocky Mountains. Sampling stations were located above and below two grazed areas which were known sources of bacterial contamination. Sampling and testing techniques were conducted using standard physical-chemical and radiational testing procedures. The above parameters were then compared to the previous biological samplings and findings of Kunkle and Meiman (1967, 1968) investigating the same stream sections. Results and conclusions are: 1. The small concentrations of physical-chemical parameters together with the accuracy and precision of the testing procedures would not allow a rigorous statistical analysis. 2. No daily or seasonal correlation was observed between the physical-chemical parameters measured and the findings of Kunkle and Meiman (1967, 1968). 3. The extinction of radiation within the stream followed the radiation decay law I = Ioe-bx. The beta coefficients, b, are determined by the equation b = -.31988 + .0952352 1/x, + .28591 x, (x = wavelength, x1 = depth cm). 4. The intensity of ultraviolet energy in the sample streams was sufficient to cause a diurnal cycling pattern in bacteria concentration. 5. Variations in the measured physical-chemical parameters were not sufficient to account for the increase in bacterial concentrations below a grazed irrigated area. This suggests that bacteria were directly introduced into the stream, rather than increasing due to a more favorable nutrient environment.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Water quality -- Colorado; Water -- Microbiology